Nilai-Nilai Pendidikan Agama Hindu Dalam Upacara Nyewu - Putu Budiadnya (Jayapangus Press, 2019)
Death means the relationship with the world in fact has been broken, Ida Sang Hyang Widhi, the creator of birth and death who has the authority to determine the status of the age limit, which cannot be predicted by ordinary people, when the right time passes to the afterlife according to the will, charity and karma. So, death is a necessity of human life, which is then each nation, religion, the tribe has its own way of giving their final respect as humans who have cultural civilizations. Just like the Nyewu ceremony in Surakarta City. There are many things studied in this study, namely: the form of the implementation of the Nyewu ceremony, the functions and meanings contained in the Nyewu ceremony, what values of Hindu religious education are contained in the Nyewu ceremony. To achieve the objectives of this study, an ethnographic approach was used using qualitative methods. In revealing the research used Structural Functionalism Theory, Symbolic Interactional Theory and Behaviorism Theory. Data is collected by observation, interview, and literature study. Ceremony which is the implementation of Pitra Yadnya. According to the Manusmsriti book based on the way the ceremony is performed, it is classified as a Prasita ceremony. There are several functions contained in this ceremony, namely religious function, social function, cultural preservation function, Nyewu ceremony, as part of Javanese culture, which contains very noble values and national cultural values as ancestral heritage that has been passed down through generations and inherited from the previous generation. The noble values contained in the ritual ceremony related to the teachings of Hinduism are the core of the value of Hinduism education, which is described in the Tri Kerangka Dasar Agama Hindu (tattwa, susila, upacara) as the basic concept of Hindu religious education. The value of tattwa education in the implementation of the Nyewu ceremony, among others: five beliefs in Hinduism namely Panca Sradha. The value of moral education in the implementation of the Nyewu ceremony, is the application of the teachings of Tri Kaya Parisudha. The value of Hinduism event education that can be gleaned from the implementation of the Nyewu ceremony is a form of application of its five principles. The application of the noble values of the Nyewu ceremony is an implementation of Hinduism based on the sacred teachings of the Vedas, because these values serve as guidelines for Hindus in particular.